A Gantry Crane Control Using ADRC and Input Shaping - Do, Trong Hieu; Hoang, Van Thang; Tran, Van Tung; Nguyen, Tri Kien; Duong, Minh Duc (Old Journal, 2018)
Gantry cranes are wildly used in various fields such as industry and transportation. There are various approaches to control cranes, but most of them are difficult in design and implementation in practice. Input shaping technique in combination with traditional PID controller is a practical approach but its performance is easily degraded by disturbance and parameter uncertainty. This paper proposes ADRC in combination with Input shaping approach in which ADRC is used to reject disturbance while keeping the simplicity in design as PID controller, and Input shaping plays the role of vibration suppression. Simulations show the effectiveness of the proposed approach.